Polycyclic tetrahydroxanthones from Streptomyces chrestomyceticus BCC 24770. Issue 5 (4th February 2016) - Bunyapaiboonsri, Taridaporn; Lapanun, Sanisa; Supothina, Sumalee; Rachtawee, Pranee; Chunhametha, Suwanee; Suriyachadkun, Chanwit; Boonruangprapa, Tanapong; Auncharoen, Patchanee; Chutrakul, Chanikul; Vichai, Vanicha
Abstract: Three polycyclic tetrahydroxanthones, chrestoxanthones A−C, together with known albofungin and chloroalbofungin were isolated from the actinomycete Streptomyces chrestomyceticus BCC 24770. Their structures were elucidated by extensive spectroscopic analyses. Chrestoxanthone A was active against Curvularia lunata and Alternaria brassicicola, while all other isolated metabolites displayed broad antifungal activities against C. lunata, A. brassicicola, Colletotrichum capsici, and Colletotrichum gloeosporioides. Graphical abstract: